Heat-resistant and shock-resistant stopper rod made of recycled materials and preparation method thereof
By using a combination of modified actolite-phenolic resin and a specific graded aluminum carbonaceous recovery material in the plug rod, the problem of short service life of the aluminum carbonaceous recovery material plug rod is solved, and efficient continuous pouring time of the plug rod is achieved Extension and performance improvement solve the problems of waste of resources and environmental protection.
Patent Information
- Application Number
- CN202411464910.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-14
AI Technical Summary
The service life of the plug rods made of existing aluminum carbonaceous recycling materials is short, especially in low-calcium content steel, which does not exceed 150 minutes, which is much shorter than the service life of traditional plug rods, resulting in waste of resources and environmental protection problems.
50-64% aluminum carbonaceous recycling material, 15-20% corundum, 1.5-3% aluminum magnesium spinel, 3-5% silicon carbide micropowder, 0.25-0.5% zirconium bored and 14-21% modification accumulation The combination of trolite-phenolic resins is made into heat-resistant and shock-resistant plug rods through specific grading and sintering processes. The modified trolite-phenolic resin disperses aluminum and trolite nanoscale through in-situ intercalation polymerization, which enhances the nanoscale of the aluminum and trolite. Viscosity and wetting properties promote sintering and pore filling, and improve the mechanical and oxidation resistance of the plug rod.
The efficient addition of aluminum carbonaceous recovery material in the plug rod is achieved, extending the continuous pouring time of the plug rod to more than 1000 minutes, improving the overall mechanical properties and thermal shock resistance of the plug rod, reducing porosity and oxidation Diffusion significantly improves the service life of the plug rod.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of refractory materials, and more particularly to a heat-resistant and shock-resistant plug rod made of recycled materials and a preparation method thereof. Background Art
[0002] The stopper rod in the continuous casting equipment is an important refractory material for controlling the flow rate of molten steel. Since the working environment of the stopper rod is harsh and it cannot be directly replaced, its service life directly affects the life of the tundish, and thus affects the continuous casting efficiency. The stopper rod can be selected from aluminum carbon, magnesium carbon and zirconium carbon materials according to the type of steel being cast. When the calcium content in the molten steel is less than 20ppm, the aluminum carbon stopper rod without SiO2 can be continuously cast for 800min; when the calcium content in the molten steel is greater than 25ppm, severe erosion will occur after 200min of continuous casting. The service life of the stopper rod is short and it is a disposable consumable. The annual consumption of stopper rods in my country is gradually increasing. Therefore, with the gradual reduction of resources and the increasing environmental protection requirements, it is of great significance to effectively recycle the discarded refractory stopper rods.
[0003] In the related art, CN104692815A discloses a thermal shock resistant integral stopper rod for continuous casting with post-production recycled materials and its preparation method. In this method, 10-50wt% aluminum carbon recycled materials are added, and then combined with fused corundum, graphite, silicon carbide and phenolic resin, and then fired in a reducing atmosphere after static pressing. However, it was found in actual production and use that the stopper rod produced by this method has a short continuous casting time. For low-calcium molten steel, the casting time does not exceed 150 minutes, which is much shorter than the service life of traditional stopper rods. Summary of the invention
[0004] In order to solve the problem of short service life of stopper rods containing aluminum carbon recycled materials, the present application provides a heat-resistant and shock-resistant stopper rod made of recycled materials and a preparation method thereof.
[0005] In the first aspect, the present application provides a heat-resistant and shock-resistant plug rod made of recycled materials, which adopts the following technical solution: A heat-resistant and shock-resistant plug rod made of recycled materials, comprising the following components by weight percentage: 50-64% aluminum carbon recycled material, 15-20% corundum, 1.5-3% aluminum magnesium spinel, 3-5% silicon carbide powder, 0.25-0.5% zirconium boride, 14-21% modified rectorite-phenolic resin; The gradation composition of the aluminum carbonaceous recycled material is as follows: 50 =1μm accounts for 20~30%, D 50 =20μm accounts for 50~70%, D 50 =100μm accounts for 0~20%; The modified rectorite-phenolic resin is prepared according to the following steps: adding aluminum isopropoxide after phenol is dissolved, stirring and heating to 50-70°C, keeping the temperature for reaction for 10-50 minutes, then adding rectorite, keeping the temperature for reaction for 1-3 hours, finally adding organic amine and polyformaldehyde, heating to 70-95°C, reacting for 1-3 hours, cooling and distilling under reduced pressure to obtain the modified rectorite-phenolic resin.
[0006] By adopting the above technical scheme, the aluminum carbonaceous recycled material comes from the discarded aluminum carbonaceous stopper rods. The discarded aluminum carbonaceous stopper rods are subjected to surface ash removal, slag layer and penetration layer removal, crushing, grinding and drying. After being homogenized with corundum, aluminum magnesium spinel, silicon carbide powder and zirconium boride according to a specific grading, modified rectorite-phenolic resin is added as a binder, filled into a mold, sintered and formed to obtain a heat-resistant and shock-resistant stopper rod.
[0007] Aluminum carbonaceous recycled materials are used to partially replace corundum raw materials and graphite raw materials. Aluminum carbonaceous recycled materials contain some pseudo particles, which are a mixture of various materials. Refractory materials added with pseudo particles are prone to secondary crushing of pseudo particles during the mixing stage. Therefore, the grading ratio of aluminum carbonaceous recycled materials and the corresponding average particle size are controlled to reduce the content of pseudo particles. The performance of aluminum carbonaceous recycled materials is similar to that of traditional refractory raw materials, thereby increasing the proportion of aluminum carbonaceous recycled materials added to the stopper rod raw materials.
[0008] Modified rectorite-phenolic resin uses the method of in-situ intercalation polymerization to introduce aluminum and rectorite into the polycondensate of phenol and formaldehyde, so that the rectorite flakes can be dispersed at the nanoscale in the phenolic resin matrix. There are ion exchange sites on the rectorite surface of the modified rectorite-phenolic resin, which can adsorb magnesium aluminum spinel, corundum, and aluminum carbon recycled materials, and the main raw materials of the stopper rod can be fully dispersed. Magnesium aluminum spinel and rectorite flakes are filled in aluminum carbon recycled materials and corundum. During the sintering process of the stopper rod, alumina is dissolved in the spinel and secondary spinelization occurs; alumina and rectorite flakes form mullite and other phases to fill the gaps between the stopper rod raw material particles; the larger pores of the aluminum carbon recycled materials provide space for secondary spinelization and space for some rectorites to expand, achieving a dynamic balance between secondary spinelization and pore filling. In addition, after the phenolic resin is modified with rectorite and aluminum isopropoxide, its viscosity decreases and its fluidity is excellent, so it can better infiltrate aluminum carbon recycled materials, corundum and aluminum magnesium spinel, and fill in the stopper rod raw material particles; during the pyrolysis process, the aluminum element and the mullite phase contribute to the graphitization of pyrolytic carbon at high temperature, promote the sintering of the stopper rod, overcome the defect of increased sintering difficulty caused by the addition of high-melting point zirconium boride, the apparent porosity of the stopper rod decreases, and the overall mechanical properties are excellent.
[0009] Zirconium boride and silicon carbide work together to form zirconium oxide. Zirconium oxide and secondary spinel layer give the stopper rod better slag resistance. Part of silicon carbide easily combines with boron to form borosilicate in the low temperature section of the sintering process, reducing the volatilization of boron oxide. At the same time, borosilicate hinders the diffusion of oxygen into the interior of the stopper rod, improving the overall oxidation resistance of the stopper rod.
[0010] Silicon carbide itself has a high thermal conductivity and can transfer heat evenly to all parts of the stopper rod; at the same time, combined with the lamellar structure of the rectorite, it gives the inside of the stopper rod better seismic stability, so the stopper rod can also have excellent thermal shock stability.
[0011] After actual testing, it was found that molten steel with a calcium content of less than 20 ppm can be continuously poured, and stopper rods containing aluminum carbon recycled materials can be continuously poured for more than 1000 minutes.
[0012] Furthermore, the molar ratio of phenol, aluminum isopropoxide, rectorite and paraformaldehyde in the modified rectorite-phenolic resin is 1:(0.01-0.04):(0.02-0.04):(1.1-1.4).
[0013] Furthermore, the molar ratio of phenol, aluminum isopropoxide, rectorite and paraformaldehyde in the modified rectorite-phenolic resin is 1:0.02:0.04:1.2.
[0014] By adopting the above technical scheme, the proportions of the various raw materials in the modified rectorite-phenolic resin are adjusted, thereby controlling the improvement of the residual carbon rate of the modified rectorite-phenolic resin, and the phenolic resin can be fully pyrolyzed to connect the various raw material particles of the stopper rod, thereby increasing the overall strength of the stopper rod and improving the thermal shock resistance of the stopper rod.
[0015] Furthermore, the solvent for dissolving the phenol is tetrahydrofuran, and the amount of tetrahydrofuran added is 50 to 90 wt % of the amount of phenol added.
[0016] Furthermore, the amount of the organic amine added is 5 to 10 wt % of the amount of phenol added.
[0017] By adopting the above technical solution, tetrahydrofuran is used as a solvent, an organic amine is used as a catalyst, and the organic amine and tetrahydrofuran are controlled within a moderate ratio, thereby adjusting the carbon residue rate of the stopper rod.
[0018] Furthermore, the gradation composition of the aluminum carbonaceous recycled material is as follows: 50 =1μm accounts for 25%, D 50 =20μm accounts for 70%, D 50 =100μm accounts for 5%.
[0019] Furthermore, the average particle size of the silicon carbide powder is in the range of 0.5 to 1 μm, the average particle size of the corundum is in the range of 5 to 50 μm, the average particle size of the zirconium boride is in the range of 1 to 3 μm, and the average particle size of the aluminum magnesium spinel is in the range of 50 to 100 μm.
[0020] By adopting the above technical solution, the grading composition of each raw material is adjusted so that raw materials with excellent slag resistance such as spinel and zirconium boride are mainly distributed outside the stopper rod, while antioxidant materials such as silicon carbide are mainly distributed inside the stopper rod, thereby extending the continuous casting time of the stopper rod as a whole.
[0021] Furthermore, the weight percentages of the various components are as follows: 50% aluminum carbon recycled material, 18% corundum, 2.5% aluminum magnesium spinel, 4% silicon carbide powder, 0.5% zirconium boride, and 20% modified rectorite-phenolic resin.
[0022] In a second aspect, the present application provides a method for preparing a heat-resistant and shock-resistant stopper rod made of recycled materials, which adopts the following technical solution: A method for preparing a heat-resistant and shock-resistant stopper rod made of recycled materials comprises the following steps: Mixing; Static pressure molding: the material obtained in the mixing step is placed into a mold and pressed at a pressure of 100-500Mpa; Firing. DETAILED DESCRIPTION
[0023] Unless otherwise specified, the sources of raw materials involved in the following preparation examples, embodiments and comparative examples are as follows: Recycled aluminum carbon stopper rod: waste product of the applicant's production line; Phenol: analytical grade; Aluminum isopropoxide: analytical grade; Paraformaldehyde: purity 99%, model 172, sourced from Hubei Xinghengye; Rectorite: Item No. 092, from Chenran Minerals in Lingshou County; Triethylamine: analytical grade; Fused corundum: composition: Al2O399.5wt%, Fe2O3≤0.05wt%, Na2O≤0.26wt%, MgO≤0.01wt%, K2O≤0.02wt%, CaO≤0.04wt%, SiO2≤0.1wt%, sourced from Zhengzhou Haixu Abrasives; Aluminum magnesium spinel: purity 99%, CAS number 12068-51-8, from Huaxiang Kejie; Zirconium boride: from Huawei Raycus, particle size customization: Silicon carbide powder: from Huawei Raycus, particle size customized; Phenolic resin: brand 2127-1, sourced from Hebei Zetian Chemical.
[0024] Preparation of Aluminum Carbon Recycled Material
[0025] Aluminum carbonaceous recycled material is prepared as follows: Take the recovered aluminum carbon stopper rod body part, remove the dust on the surface of the stopper rod body, then cut the stopper rod surface to a thickness of 1 cm, fully remove the slag layer and penetration layer on the surface of the stopper rod body, then put it into a jaw crusher for crushing to a size of ≤1 cm, and then put it into a grinder for grinding until the size is controlled at 1-100μm to obtain aluminum carbon recovery material.
[0026] Modified rectorite-phenolic resin is a preparation example
[0027] Preparation Example a Modified rectorite-phenolic resin is prepared as follows: Prepare phenol, aluminum isopropoxide, rectorite, and paraformaldehyde in a molar ratio of 1:0.02:0.04:1.2; Phenol was added into a reactor, heated to melt, and tetrahydrofuran was added to dissolve after complete melting. The amount of tetrahydrofuran added was 60wt% of the weight of phenol, and the mixture was stirred and dissolved at a speed of 100rpm. After the phenol was completely dissolved, aluminum isopropoxide was added, and the mixture was heated to 60°C while stirring. After reacting for 30 minutes, rectorite was added, and the mixture was kept at 60°C. The mixture was stirred and dissolved at a speed of 100rpm for 2 hours. Then add triethylamine and polyformaldehyde, the amount of triethylamine added is 8wt% of the weight of phenol, raise the temperature to 85°C, keep the temperature for 2h, cool the reaction solution to room temperature and perform vacuum distillation to obtain modified rectorite-phenolic resin.
[0028] Preparation Example bd The modified rectorite-phenolic resin is different from that of Preparation Example a in that the molar ratios of phenol, aluminum isopropoxide, rectorite and paraformaldehyde are different: In Preparation Example b, the molar ratio of phenol, aluminum isopropoxide, rectorite and paraformaldehyde is 1:0.01:0.02:1.1; In Preparation Example c, the molar ratio of phenol, aluminum isopropoxide, rectorite and paraformaldehyde is 1:0.04:0.04:1.2; In Preparation Example d, the molar ratio of phenol, aluminum isopropoxide, rectorite and paraformaldehyde is 1:0.04:0.04:1.4.
[0029] Preparation Example The difference between the modified rectorite-phenolic resin and Preparation Example a is that the added amounts of tetrahydrofuran and triethylamine are different, as follows: In Preparation Example e, the amount of tetrahydrofuran added is 50wt% of the weight of phenol, and the amount of triethylamine added is 5wt% of the weight of phenol; In Preparation Example f, the amount of tetrahydrofuran added is 90 wt % of the weight of phenol, and the amount of triethylamine added is 10 wt % of the weight of phenol.
[0030] Example
[0031] Example 1
[0032] A heat-resistant and shock-resistant plug rod made of recycled materials is made according to the following steps: Weigh out according to weight: 55 parts of aluminum carbon recycled material, 18 parts of fused corundum, 2.5 parts of aluminum magnesium spinel, 4 parts of silicon carbide powder, 0.5 parts of zirconium boride, and 20 parts of modified rectorite-phenolic resin (from Preparation Example a); Among them, the gradation size of aluminum carbon recycled materials is as follows: D 50 =1μm accounts for 25%, D 50 =20μm accounts for 70%, D 50 =100μm accounts for 5%; The average particle size of fused corundum ranges from 5 to 50 μm; The average particle size of spinel ranges from 50 to 100 μm; The average particle size of silicon carbide powder ranges from 0.5 to 1 μm; The average particle size of zirconium boride ranges from 1 to 3 μm; Mixing: Evenly mix the aluminum carbon recycled material, aluminum magnesium spinel, silicon carbide powder and zirconium boride, and then add the modified rectorite-phenolic resin; Static pressure molding: After the modified rectorite-phenolic resin is evenly mixed, the materials are poured into the mold and statically pressed at a pressure of 300MPa; Firing: nitrogen is introduced as a protective gas, and the mold is calcined in an environment with an oxygen concentration of 0.5 mol / L. The temperature is maintained at 600°C at the initial stage of calcination for 2 hours; then the temperature is raised to 1200°C and calcined for 2.5 hours; finally, the temperature is raised to 1600°C and calcined for 1 hour, then the temperature is lowered to 500°C and annealed for 3 hours; the firing is completed to obtain a heat-resistant and shock-resistant plug rod.
[0033] Embodiment 2-6 A heat-resistant and shock-resistant stopper rod made of recycled materials is different from Example 1 in that the source of the modified rectorite-phenolic resin is different, as follows: The modified rectorite-phenolic resin in Example 2 is derived from Preparation Example b; The modified rectorite-phenolic resin in Example 3 is derived from Preparation Example c; The modified rectorite-phenolic resin in Example 4 is derived from Preparation Example d; The modified rectorite-phenolic resin in Example 5 is derived from Preparation Example e; The modified rectorite-phenolic resin in Example 6 is derived from Preparation Example f.
[0034] Embodiment 7-8 A heat-resistant and shock-resistant stopper rod made of recycled materials is different from Example 1 in that the weight percentage of the raw materials is different, as follows: In Example 7, the following were weighed in parts by weight: 50.5 parts of aluminum carbonaceous recycled material, 20 parts of fused corundum, 3 parts of aluminum magnesium spinel, 5 parts of silicon carbide powder, 0.5 parts of zirconium boride, and 21 parts of modified rectorite-phenolic resin (derived from Preparation Example a); Among them, the gradation size of aluminum carbon recycled materials is as follows: D 50 =1μm accounts for 25%, D 50 =20μm accounts for 70%, D 50 =100μm accounts for 5%; The average particle size of fused corundum ranges from 5 to 50 μm; The average particle size of spinel ranges from 50 to 100 μm; The average particle size of silicon carbide powder ranges from 0.5 to 1 μm; The average particle size of zirconium boride ranges from 1 to 3 μm; In Example 8, the following were weighed in parts by weight: 64 parts of aluminum carbonaceous recycled material, 15 parts of fused corundum, 1.5 parts of aluminum magnesium spinel, 3 parts of silicon carbide powder, 0.25 parts of zirconium boride, and 16.25 parts of modified rectorite-phenolic resin (derived from Preparation Example a); Among them, the gradation size of aluminum carbon recycled materials is as follows: D 50 =1μm accounts for 25%, D 50 =20μm accounts for 70%, D 50 =100μm accounts for 5%; The average particle size of fused corundum ranges from 5 to 50 μm; The average particle size of spinel ranges from 50 to 100 μm; The average particle size of silicon carbide powder ranges from 0.5 to 1 μm; The average particle size of zirconium boride is in the range of 1 to 3 μm.
[0035] Examples 9-10 A heat-resistant and shock-resistant stopper rod made of recycled materials is different from Example 1 in that the gradation of the raw materials is different, as follows: In Example 9, the following were weighed in parts by weight: 55 parts of aluminum carbonaceous recycled material, 18 parts of fused corundum, 2.5 parts of aluminum magnesium spinel, 4 parts of silicon carbide powder, 0.5 parts of zirconium boride, and 20 parts of modified rectorite-phenolic resin (derived from Preparation Example a); Among them, the gradation size of aluminum carbon recycled materials is as follows: D 50 =1μm accounts for 30%, D 50 =20μm accounts for 50%, D 50 =100μm accounts for 20%; The average particle size of fused corundum ranges from 50 to 100 μm; The average particle size of spinel ranges from 50 to 100 μm; The average particle size of silicon carbide powder ranges from 5 to 10 μm; The average particle size of zirconium boride ranges from 5 to 10 μm; In Example 10, the following were weighed in parts by weight: 55 parts of aluminum carbonaceous recycled material, 18 parts of fused corundum, 2.5 parts of aluminum magnesium spinel, 4 parts of silicon carbide powder, 0.5 parts of zirconium boride, and 20 parts of modified rectorite-phenolic resin (derived from Preparation Example a); Among them, the gradation size of aluminum carbon recycled materials is as follows: D 50 =1μm accounts for 30%, D 50 =20μm accounts for 70%; The average particle size of fused corundum ranges from 1 to 20 μm; The average particle size of spinel ranges from 1 to 50 μm; The average particle size of silicon carbide powder ranges from 0.1 to 0.5 μm; The average particle size of zirconium boride is in the range of 0.1 to 1 μm.
[0036] Examples 11-12 A heat-resistant and shock-resistant stopper rod made of recycled materials is different from Example 1 in that the static pressing pressure in the raw material preparation step is different, as follows: In Example 11, the static pressing pressure is 100 MPa; In Example 12, the static pressing molding pressure is 500 MPa.
[0037] Comparative Example
[0038] Comparative Example 1
[0039] A stopper rod made of recycled material is made according to the following steps: Weigh according to weight: 55 parts of aluminum carbon recycled material, 18 parts of fused corundum, 2.5 parts of aluminum magnesium spinel, 4 parts of silicon carbide powder, 0.5 parts of zirconium boride, and 20 parts of phenolic resin mixture; Among them, the gradation size of aluminum carbon recycled materials is as follows: D 50 =1μm accounts for 25%, D 50 =20μm accounts for 70%, D 50 =100μm accounts for 5%; The average particle size of fused corundum ranges from 5 to 50 μm; The average particle size of spinel ranges from 50 to 100 μm; The average particle size of silicon carbide powder ranges from 0.5 to 1 μm; The average particle size of zirconium boride ranges from 1 to 3 μm; 20 parts of phenolic resin mixture are obtained by uniformly mixing phenolic resin, aluminum isopropoxide and rectorite in a molar ratio of 2.2:0.02:0.04; Mixing: Mix aluminum carbon recycled material, aluminum magnesium spinel, silicon carbide powder and zirconium boride evenly, then add phenolic resin mixture and mix evenly; Static pressure molding: Pour the evenly mixed materials into the mold and statically press them at a pressure of 300MPa; Firing: nitrogen is introduced as a protective gas, and the mold is calcined in an environment with an oxygen concentration of 0.5 mol / L. The temperature is maintained at 600°C at the initial stage of calcination for 2 hours; then the temperature is raised to 1200°C and calcined for 2.5 hours; finally, the temperature is raised to 1600°C and calcined for 1 hour, then the temperature is lowered to 500°C and annealed for 3 hours; the firing is completed to obtain a heat-resistant and shock-resistant plug rod.
[0040] Comparative Example 2 A stopper rod made of recycled materials, which is different from Example 1 in that the gradation of the aluminum-carbon recycled materials is different. The gradation of the aluminum-carbon recycled materials is as follows: D 50 =100μm accounts for 30%, D 50 =1000μm accounts for 70%.
[0041] Performance Testing
[0042] The heat-resistant and shock-resistant plug rods made in Examples 1-12 and Comparative Examples 1-2 were made into test samples, wherein Examples 1-12 and Comparative Example 1 were produced using a mold of the same shape.
[0043] 1. Production test: There are 10 test samples in each group. The calcium content in the continuously poured molten steel is. The continuous pouring time is recorded, and the average pouring time of each group of test samples is calculated.
[0044] Table 1. Test data of Examples 1-12 and Comparative Example 1
[0045] in conclusion
[0046] According to the test data, we can see that: First, Example 1 and Comparative Example 1 form a single comparison. In Comparative Example 1, rectorite, aluminum isopropoxide and phenolic resin are directly used as adhesives without modification, but the performance of the stopper rod prepared is significantly deteriorated. The reasons are: the dispersion effect of rectorite in phenolic resin is poor, the viscosity of phenolic resin increases, its fluidity is poor, and the wettability of aluminum carbonaceous recycled materials decreases; at the same time, rectorite cannot be dispersed in a nano-monolithic structure, and cannot be fully filled between the stopper rod raw material particles in the early stage. In the later firing process, the rectorite shrinks, and the apparent porosity of the stopper rod increases, resulting in a decrease in the overall mechanical properties of the stopper rod, poor seismic performance of the stopper rod, and the stopper rod is prone to breakage in a short period of time. The continuous casting time of the stopper rod is reduced to 90 minutes.
[0047] Second, Example 1 and Comparative Example 2 form a single comparison. The gradation of the aluminum-carbon recycled material in Comparative Example 2 is different. The gradation of the aluminum-carbon recycled material in Comparative Example 2 is larger. A large number of false particles and impurities appear in the aluminum-carbon recycled material during the static pressing process, which leads to secondary breakage of the stopper rod during the sintering process. The pores of the stopper rod increase, the modified rectorite-phenolic resin is difficult to infiltrate the stopper rod raw material particles, the stopper rod is easy to break, and the continuous casting time of the stopper rod is less than 1 / 3 of the continuous casting time of Example 1.
[0048] Third, Examples 1-4 form a single comparison. The amounts of rectorite and aluminum isopropoxide added in Examples 1-4 are different. Too much or too little addition of rectorite and aluminum isopropoxide will have an adverse effect on the stopper rod. When the amount of aluminum isopropoxide added is too low, although the residual carbon rate of the modified phenolic resin is increased, it is not conducive to reducing the sintering difficulty. Aluminum isopropoxide is difficult to promote the sintering of the stopper rod, resulting in a decrease in apparent porosity. Although the excessive addition of rectorite helps to increase the residual carbon rate of the stopper rod, the lamellar structure of the rectorite is difficult to fully peel off, resulting in an increase in apparent porosity during the sintering process of the stopper rod and a decrease in continuous casting time.
[0049] Fourth, by contrast between Examples 1 and 7-8, it can be seen from the test data that the higher the amount of aluminum-carbon recycled material added, the shorter the continuous pouring time. When the addition ratio of aluminum-carbon recycled material reaches more than 60, the continuous pouring time of aluminum-carbon recycled material can reach more than 1000 min.
[0050] Fifth, by contrast with Examples 1, 9-10, it can be seen from the test data that the grading of the raw materials has a greater impact on the continuous casting time of the stopper rod. The reason is that the grading of the raw materials affects the distribution of different particles of the raw materials in the stopper rod, so that raw materials with excellent slag resistance such as spinel and zirconium boride are mainly distributed outside the stopper rod, while antioxidant materials such as silicon carbide are mainly distributed inside the stopper rod, thereby extending the continuous casting time of the stopper rod as a whole.
[0051] The various technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the various technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0052] Moreover, the above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A heat-resistant and shock-resistant plug rod made of recycled materials, characterized in that: According to weight percentage, it includes the following components: 50-64% aluminum carbon recycled material, 15-20% corundum, 1.5-3% aluminum magnesium spinel, 3-5% silicon carbide powder, 0.25-0.5% zirconium boride, 14-21% modified rectorite-phenolic resin; The gradation composition of the aluminum carbonaceous recycled material is as follows: 50 =1μm accounts for 20~30%, D 50 =20μm accounts for 50~70%, D 50 =100μm accounts for 0~20%; The modified rectorite-phenolic resin is prepared according to the following steps: adding aluminum isopropoxide after phenol is dissolved, stirring and heating to 50-70°C, keeping the temperature for reaction for 10-50 minutes, then adding rectorite, keeping the temperature for reaction for 1-3 hours, finally adding organic amine and polyformaldehyde, heating to 70-95°C, reacting for 1-3 hours, cooling and distilling under reduced pressure to obtain the modified rectorite-phenolic resin.
2. The heat-resistant and shock-resistant stopper rod made of recycled materials according to claim 1, characterized in that: The molar ratio of phenol, aluminum isopropoxide, rectorite and paraformaldehyde in the modified rectorite-phenolic resin is 1:(0.01-0.04):(0.02-0.04):(1.1-1.4).
3. The heat-resistant and shock-resistant stopper rod made of recycled materials according to claim 2, characterized in that: The molar ratio of phenol, aluminum isopropoxide, rectorite and paraformaldehyde in the modified rectorite-phenolic resin is 1:0.02:0.04:1.
2.
4. The heat-resistant and shock-resistant stopper rod made of recycled materials according to claim 1, characterized in that: The solvent for dissolving the phenol is tetrahydrofuran, and the amount of tetrahydrofuran added is 50-90wt% of the amount of phenol added.
5. The heat-resistant and shock-resistant stopper rod made of recycled materials according to claim 1, characterized in that: The amount of the organic amine added is 5-10 wt % of the amount of phenol added.
6. The heat-resistant and shock-resistant stopper rod made of recycled materials according to claim 1, characterized in that: The gradation composition of the aluminum carbonaceous recycled material is as follows: 50 =1μm accounts for 25%, D 50 =20μm accounts for 70%, D 50 =100μm accounts for 5%.
7. The heat-resistant and shock-resistant stopper rod made of recycled materials according to claim 1, characterized in that: The average particle size of the silicon carbide powder is in the range of 0.5 to 1 μm, the average particle size of the corundum is in the range of 5 to 50 μm, the average particle size of the zirconium boride is in the range of 1 to 3 μm, and the average particle size of the aluminum magnesium spinel is in the range of 50 to 100 μm.
8. The heat-resistant and shock-resistant stopper rod made of recycled materials according to claim 7, characterized in that: 50% aluminum carbon recycled material, 18% corundum, 2.5% aluminum magnesium spinel, 4% silicon carbide powder, 0.5% zirconium boride, 20% modified rectorite-phenolic resin.
9. The method for preparing a heat-resistant and shock-resistant stopper rod made of recycled materials according to any one of claims 1 to 8, characterized in that: The steps include: Mixing; Static pressure molding: the material obtained in the mixing step is placed into a mold and pressed at a pressure of 100-500Mpa; Firing.
Citation Information
Patent Citations
Formula of caput of composition type stopper
CN101050104A
Continuous casting thermal shock-resistant monoblock stopper added with recycled materials, and preparation method thereof
CN104692815A
High-strength wear-resisting idler wheel for agricultural machinery
CN107191472A
Phenolic resin for carbon-containing refractory material and preparing method of phenolic resin
CN107540804A
Low-carbon ultra-low-carbon aluminum-carbon fired refractory material and preparation method thereof
CN110330319A